STUDI LITERATUR: DAMPAK OBJEK WISATA RELIGI DAN PEMBERDAYAAN MASYARAKAT LOKAL TERHADAP PERUBAHAN SOSIAL-EKONOMI - Rohmat Wardiman (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
This study aims to evaluate the contribution of religious tourism destinations toward local community welfare and analyze the socio-economic impacts arising from interactions between visitors and local residents. The methodology employed is a Systematic Literature Review (SLR), conducted through structured stages of identification, screening, and in-depth analysis of relevant studies. Findings indicate that religious tourism activities significantly influence the improvement of living standards through job creation, MSME development, and increased income. Furthermore, the study identifies a shift in community behavior toward more participatory involvement in cultural heritage preservation and creative economy management. The reciprocal relationship between tourists and local communities creates mutually beneficial social dynamics. The limitation of this study lies in the scope of literature, which is confined to journal articles indexed in specific digital databases and a geographical focus primarily centered on the Indonesian context; therefore, generalizing the findings to a global context may require a broader review. This research is expected to serve as a reference for destination managers and governments in formulating sustainable, community-based religious tourism empowerment policies.